(untitled) (Revista Contexto & Educação, 2025)
Brazilian public universities have an important role in achieving the 2030 Agenda. Therefore, the objective of this article was to verify the evidence of appropriation of the zero waste approach in considered public universities. A qualitative approach was carried out, with bibliographic and documentary research based on the UI GreenMetric international ranking. The results of the bibliographical research indicate that universities must popularize the zero waste concept, incorporate the circular economy from different sources and that campuses can serve as a living elaborative model for multidimensional sustainability practices, including partnerships with government organizations and municipal managers. As for documentary research, the universities researched come from, although they are considered harmful, they have not yet incorporated academic and management practices to internalize sustainability. In the results of the lexical analysis, the term governance draws attention, showing its importance in the contemporary context of the research on Brazilian public universities, which can help implement the zero waste concept.